Ein wenig erforschter aksumitischer Platz in Däbrä Gärgiš, ʿAddi Daʿǝro, Tǝgray - Smidt, Wolbert G.C. (Aethiopica, 2007)
This article focuses on an ancient, yet unexplored Aksumite site in Eastern Tigray, visited during an ethnohistorical research carried out between 2004 and 2006. It lies at an unknown ancient (Aksumite) route and might have been the seat of a provincial leader. The site lies in an area not known yet for Aksumite ruins, as it lies rather remote from main routes today. The site consists of a stelae and a ruin hill with remains of an unidentified ancient building. This publication aims at awaking interest in research on that site, including researching oral sources. The interest lies in the possibility to learn more about the provinces of Aksum.